Effects of sodium hypochlorite on periodontal healing after tooth replantation - histomorphometric study in rats (Pesquisa Odontológica Brasileira, 2000)
The aim of the present study was to examine the influence of 1% sodium hypochlorite on periodontal healing after tooth replantation. Rats incisors were extracted, maintained in the environment during 30 minutes, then immersed in 1% sodium hypochlorite for 30 minutes. In the control group, the teeth were maintained in distilled water. The animals were sacrificed after 10, 30 and 60 days. Transversal slices of the teeth were obtained and histologically processed through the hematoxylin and eosin technique. Slices from the cervical, middle and apical thirds of each tooth were selected for the analysis. The slices were projected and outlined. The tissues observed on the dental surfaces were measured with an image analysing system (Mini-Mop, Carl Zeiss). In the 10-day treated group, the main characteristic observed was a connective tissue arranged parallelly to the root surface, although not attached to it. After 30 and 60 days, the connective tissue was reduced and an increase of ankylosis was observed, as well as replacement resorption. A limited periodontal ligament reattachment was also observed. In the control group, the periodontal ligament was preserved in about 15% to 17% of the root surface after 30 and 60 days, and the resorption areas were deeper than in the treated group. It was concluded that 1% sodium hypochlorite allowed an increase of the ankylosed root surface and a limited periodontal ligament reattachment, but did not avoid replacement resorption.